2013
DOI: 10.3960/jslrt.53.87
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Hyaline Vascular-Type Castleman's Disease With Thrombocytopenia, Anasarca, Fever, and Systemic Lymphadenopathy

Abstract: Recently, atypical Castleman's disease (CD) was reported in Japan. This disease is considered as TAFRO syndrome or non-idiopathic plasmacytic lymphadenopathy (IPL), a constellation of clinical symptoms, namely, thrombocytopenia, anasarca, fever, reticulin fibrosis, and organomegaly without hyper-γ-globulinemia. Histopathologically, this disease is similar to hyaline vascular (HV)-type CD. Here, we present a 43-year-old Japanese woman meeting the clinical criteria of TAFRO syndrome who was successfully treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 30 publications
(31 reference statements)
2
52
0
Order By: Relevance
“…Typically, thrombocytopenia is attributed to either decreased platelet production or increased platelet destruction. Previous studies reported 11 cases of TAFRO syndrome and elevated antiplatelet antibodies (Table 1) [5, 6, 11-18]. Similar to our case, anti-GPIIb/IIIa antibody was positive in 1 case [5] and anti-HLA class I antibody was positive in 2 cases [12].…”
Section: Discussionsupporting
confidence: 73%
“…Typically, thrombocytopenia is attributed to either decreased platelet production or increased platelet destruction. Previous studies reported 11 cases of TAFRO syndrome and elevated antiplatelet antibodies (Table 1) [5, 6, 11-18]. Similar to our case, anti-GPIIb/IIIa antibody was positive in 1 case [5] and anti-HLA class I antibody was positive in 2 cases [12].…”
Section: Discussionsupporting
confidence: 73%
“…It is interesting that the levels of IL-6 and VEGF in the ascitic fluid of our patient were markedly higher than the levels in his serum and plasma. One previous case has been reported of a patient with severe anasarca and markedly elevated IL-6, suggesting systemic inflammation of the serosa [3]. …”
Section: Discussionmentioning
confidence: 99%
“…There are no adolescent cases reported to date, and this is the first case of a young patient with an apparent diagnosis of TAFRO syndrome. All patients were treated with steroids and some improved with the addition of cyclosporine A [2,6] or TCZ [3,4] with rituximab therapy [3]. Unfortunately, three of the eight patients died [5,6], indicating that this syndrome sometimes results in a fatal outcome in spite of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…11,14,[16][17][18][19][20] iMCD patients without TAFRO syndrome typically have thrombocytosis, hypergammaglobulinemia, and less severe fluid accumulation. This non-TAFRO group has been called idiopathic plasmacytic lymphadenopathy with polyclonal hyperimmunoglobulinemia or IPL-type.…”
Section: Introductionmentioning
confidence: 99%